Let's find the indefinite integral of \(\dfrac{e^x}{x}.\)

....I know it's \(\text{Ei}(x)+C\) but let's do it anyways

So firstly, I'm gonna let \(\dfrac{1}{x}=t,\) leading us to \(x=\dfrac{1}{t}.\)

Differentiating gives \(dx=-\dfrac{1}{t^2}dt,\) and therefore:

\[\begin{align} \int \frac{e^x}{x}dx &= \int \frac{1}{x}\cdot e^x dx \\ & =\int t \cdot e^{\frac{1}{t}}\cdot\left(-\dfrac{1}{t^2}\right) dt \\ & =- \int \frac{e^{\frac{1}{t}}}{t} dt \\ & =- \int \frac{e^{\frac{1}{x}}}{x} dx \\ \end{align}\]

From above, we get:

\(\displaystyle \int \frac{e^x}{x} dx + \int \frac{e^{\frac{1}{x}}}{x} dx = 0 + (C)\)

\(\displaystyle \int \frac{e^x+e^{\frac{1}{x}}}{x} dx = 0 + (C)\)

Differentiating both sides gives:

\(\displaystyle \frac{e^x + e^{\frac{1}{x}}}{x} = 0\)

....then...

\(\displaystyle e^x+e^{\frac{1}{x}}=0\)...?!

I didn't expect this to happen but I have this terrible migraine to think more deeply about this ._.

Yes I am stupid, sorry ;;>_>

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest\(\int \frac{e^{1/t}}{t} dt \neq \int \frac{e^{1/x}}{x} dx\). Remember \(x=\frac{1}{t}\), and we are talking about indefinite integrals.

Log in to reply

Yeah... Someone told me that in the below chain of comments and...

....I feel even dumber now. x'D

Log in to reply

You forgot about the arbitrary constant of integration.

Log in to reply

Hmm...

then let \(\displaystyle \int \frac{e^x}{x}dx+\int \frac{e^{\frac{1}{x}}}{x}dx=C,\) but when you

differentiateboth sides,\(\dfrac{e^x+e^{\frac{1}{x}}}{x}=0.\)

Log in to reply

[ this comment is wrong ]

Log in to reply

The integral of 1 - cos^2 x is

The integral of 1 - the integral of cos^2 x

= x - the integral of cos^2 x + C

Therefore

The integral of sin^2 x + the integral of cos^2 x = x + C

Differentiate and we get

sin^2 x + cos^2 x = 1

Log in to reply

Log in to reply

Summoning the great @Mark Hennings

Log in to reply

Log in to reply

Log in to reply